Clinical and biological differences between cryoglobulinaemic and hypergammaglobulinaemic purpura in primary Sjögren's syndrome: results of a large multicentre study. (January 2015) - Quartuccio, L; Isola, M; Baldini, C; Priori, R; Bartoloni, E; Carubbi, F; Gregoraci, G; Gandolfo, S; Salvin, S; Luciano, N; Minniti, A; Alunno, A; et al.
Abstract : Objectives: To determine the clinical and laboratory differences between cryoglobulinaemic and hypergammaglobulinaemic purpura in primary Sjögren's syndrome (pSS), in a large Italian multicentre cohort. Method: Patients were selected according to the following criteria: fulfilling the American–European classification criteria for pSS, serum cryoglobulin and gammaglobulin levels evaluated, and lack of hepatitis C virus (HCV) infection. Multinomial analyses were performed by distinguishing three groups of pSS: (i) purpura associated with cryoglobulinaemic vasculitis (CV), (ii) purpura associated with hypergammaglobulinaemic vasculitis (HGV), and (iii) pSS patients without purpura (pSS controls). Patients with purpura but without cryoglobulins or hypergammaglobulinaemia were excluded. Results: A total of 652 patients were enrolled in this study. Group 1/CV comprised 23/652 patients (3.53%), group 2/HGV 40/652 patients (6.13%), and group 3/pSS controls 589/652 (90.34%). The three groups were found to be significantly different from each other (post-estimation test: group 1/CV vs. group 3/pSS controls: p < 0.0001; group 1/CV vs. group 2/HGV: p = 0.0001; group 2/HGV vs. group 3/pSS controls: p = 0.0003), thus confirming the different phenotypes of purpura in pSS.Multivariate analyses revealed that peripheral neuropathy (p < 0.001), low C4 (p < 0.001), leucopaenia (p = 0.01), serum monoclonal component (p = 0.02), and the presence of anti-SSB/La antibodies (p = 0.02) characterized CV whereas rheumatoid factor (p = 0.001), leucopaenia (p = 0.01), serum monoclonal component (p = 0.01), and anti-SSA/Ro antibodies (p = 0.049) were significantly associated with HGV. Lymphoma was associated only with CV. Conclusions: HGV is a cutaneous vasculitis, related to a benign B-cell proliferation, whereas CV is a systemic immune complex-mediated vasculitis with complement activation and a higher risk of lymphoma, thus confirming CV but not HGV as a prelymphomatous condition in pSS.